2018
DOI: 10.1002/ange.201801452
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis with Pnictogen, Chalcogen, and Halogen Bonds

Abstract: Halogen-and chalcogen-based s-hole interactions have recently received increased interest in non-covalent organocatalysis.H owever,t he closely related pnictogen bonds have been neglected. In this study,w ei ntroduce conceptually simple,n eutral, and monodentate pnictogenbonding catalysts.S olution and in silico binding studies, together with high catalytic activity in chloride abstraction reactions,yield compelling evidence for operational pnictogen bonds.T he depth of the s holes is easily varied with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 76 publications
1
77
0
Order By: Relevance
“…[44][45][46] Secondly, we and others have shown that the Sb-H bonds can break heterolytically in the presence of a Lewis acids. 26 Finally, even formally neutral Sb(III) centers can exhibit substantial electrophilicity, [47][48][49] allowing autoionization processes to proceed. 43 Radical mechanism D involves H-atom abstraction from 1H by the acetylene (TSD1) to…”
Section: Considered Mechanismsmentioning
confidence: 99%
“…[44][45][46] Secondly, we and others have shown that the Sb-H bonds can break heterolytically in the presence of a Lewis acids. 26 Finally, even formally neutral Sb(III) centers can exhibit substantial electrophilicity, [47][48][49] allowing autoionization processes to proceed. 43 Radical mechanism D involves H-atom abstraction from 1H by the acetylene (TSD1) to…”
Section: Considered Mechanismsmentioning
confidence: 99%
“…This motif thus offers for chalcogen bonds what bipyridine lone pairs offer for cation binding and bipyrroles for anion binding with hydrogen bonds. Anion transport and catalytic activities increased with increasing depth of the σ holes in electron‐deficient DTTs such as 5 compared to 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, despite the development of excellent proof-ofconcept XB-catalyzed reactions by multiple research groups [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] , protocols whereby XB catalysis shows clear catalytic advantages in over conventional thiourea catalysis is lacking 21 . Moreover, a conceivable configurational advantage pertaining to XB catalysis would involve the ease of σ-hole tunability via halogen swapping to accommodate challenging substrates-an advantage not well adoptable in thiourea catalysis due to strict requirements of hydrogen atoms for dual HB activation.…”
mentioning
confidence: 99%